2021
DOI: 10.5937/aaser2151011c
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of factors that influenced consumers' decision to online shop organic food during Covid-19

Abstract: There is a significant amount of research in the world on the factors that influence consumers' decision to buy organic food using traditional sales channels. There is also a lot of research related to the factors that influence consumer decision to online shop groceries. However, to our knowledge, there is an extremely modest amount of research on how and why consumers decide to online shop organic food. The Covid-19 pandemic has led to an increase in consumer propensity to shop online, so this topic has gain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
1
0
2
Order By: Relevance
“…The high willingness coincides with the growing demand for organic produce in the last ten years and the consumer willingness to pay more for such produce [32], even in times of the COVID-19 pandemic [33]. The findings have shown that wineries in the Republic of Serbia are aware of the importance of the environmentally responsible production and of the effects that can be achieved [34].…”
Section: Discussionmentioning
confidence: 74%
“…The high willingness coincides with the growing demand for organic produce in the last ten years and the consumer willingness to pay more for such produce [32], even in times of the COVID-19 pandemic [33]. The findings have shown that wineries in the Republic of Serbia are aware of the importance of the environmentally responsible production and of the effects that can be achieved [34].…”
Section: Discussionmentioning
confidence: 74%
“…The global sales of organic milk and milk products in the last years have seen significant growth and the demand for organic products on the market is higher than supply. Global tendencies point to the fact that the demand for organic dairy products has registered significant growth even in the period of the COVID-19 pandemic (Ćirić et al, 2021;.…”
Section: Introductionmentioning
confidence: 99%
“…Basha and D. Lal (2019) navode da su ti faktori: briga o okruženju, o zdravlju, kvalitet proizvoda, podrška lokalnim proizvođačima, bezbednost i poverenje i subjektivne norme. Međutim, u poslednje vreme, sa intenzivnim razvojem interneta i na njemu zasnovanim tehnologijama, ističu se još neki od činilaca, svojstveni online okruženju, koji mogu uticati na stavove i izbor hrane organskog porekla (Hasanov & Khalid, 2015;Ćirić, Ignjatijević, Ilić, Puvača & Brkanlić, 2021). Tako, recimo, M. Ćirić et al (2021), prilikom ispitivanja online kupovine hrane organskog porekla, u razmatranje uzimaju i karakteristike web sajta.…”
unclassified
“…Potrebno je naglasiti da razvoj online trgovine pruža nove mogućnosti prodaje za brojne proizvode, među kojima su i oni organskog porekla (Yue, Liu & Wei, 2017;Tariq, Wang, Tanveer, Akram & Akram, 2019;Ćirić et al, 2020). Aktuelna pandemijska situacija dodatno je uticala na to da potrošači organske hrane izbegavaju kupovinu u samim radnjama, već se baziraju na online kupovinu (Ćirić et al, 2020;Lin, Li & Guo, 2021;Ćirić et al, 2021), čime se dodatno opravdava izbor istraživačke koncepcije modela u ovom radu. Jedno od istraživanja, koje je sprovedeno na teritoriji RS, pokazalo je da je pandemija rezultirala povećanjem procenta potrošača koji organsku hranu kupuju online putem (Ćirić et al, 2020).…”
unclassified